On the Effects of Entry under Flexible Production Techniques: An Example of Quasi-Anticompetitiveness - Emanuele Bacchiega; Paolo G. Garella (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
We study reactions to entry in a Cournot model, contrasting the case where firms are endowed with unchangeable technologies against that where technologies are flexible. By the latter we mean that firms can change the installed production technique at zero cost (fully flexible technologies). We show that when firms are technologically flexible, entry can increase equilibrium prices. The analysis is cast in a short- run time horizon to simplify exposition, but its predictive power may better relate to the long run.
Keywords: 330